2014
DOI: 10.3892/or.2014.3311
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-224-5p is associated with the original cisplatin resistance of ovarian papillary serous carcinoma

Abstract: Chemoresistance is a major challenge to successful chemotherapy of ovarian cancer, which represents the leading cause of mortality from gynecologic malignancies. We demonstrated that overexpression of miR-224-5p in ovarian cancer patients is associated with platinum-based chemoresistance using miRNA microarray analysis and quantitative real-time polymerase chain reaction (qRT-PCR) validation in vivo, as well as in 4 human ovarian cancer cell lines (C13/OV2008; A2780CP/A2780S) in vitro. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…MMP-2 Increase celastrol inhibitory effect on cell migration and invasion Hepatocellular Li et al [56] MMP-9 Increase celastrol inhibitory effect on cell migration and invasion Hepatocellular Li et al [56] API-5 Amplify radiation sensitivity Glioblastoma Upraity et al [57] PDGFR A biomarker for the prognosis of sorafenib-treated patients Hepatocellular Gyöngyösi et al [58] PRKCD Increase resistance to cisplatin Ovarian Zhao et al [59] CD59 Predict the response and outcome of patients treated with R-CHOP Lymphoma Song et al [60] Tumor Biol.…”
Section: Conflicts Of Interestmentioning
confidence: 98%
See 1 more Smart Citation
“…MMP-2 Increase celastrol inhibitory effect on cell migration and invasion Hepatocellular Li et al [56] MMP-9 Increase celastrol inhibitory effect on cell migration and invasion Hepatocellular Li et al [56] API-5 Amplify radiation sensitivity Glioblastoma Upraity et al [57] PDGFR A biomarker for the prognosis of sorafenib-treated patients Hepatocellular Gyöngyösi et al [58] PRKCD Increase resistance to cisplatin Ovarian Zhao et al [59] CD59 Predict the response and outcome of patients treated with R-CHOP Lymphoma Song et al [60] Tumor Biol.…”
Section: Conflicts Of Interestmentioning
confidence: 98%
“…In ovarian cancer, ectopic expression of miR-224-5p is related to platinum-based chemoresistance. Overexpression of miR-224-5p increases chemoresistance to cisplatin via apoptosis reversion at least in part by downregulating PRKCD in ovarian cancer cells [59]. In diffuse large B cell lymphoma (DLBCL) patients, the expression levels of miR-224 and its target CD59 can predict the response and outcome of patients treated with rituximab, cyclophosphamide, adriamycin, vincristine, and prednisone (R-CHOP) [60] (Table 1).…”
Section: Clinical Significance Of Mir-224mentioning
confidence: 99%
“…By targeting p21, it participated in cell cycle regulation at the G1/S checkpoint (236). miR-224 could induce resistance to cisplatin in lung and ovarian cancer cell lines (47, 237). In contrast, miR-224 promoted cisplatin sensitivity in osteosarcoma resistant cells by targeting Rac1 (238).…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 99%
“…Recent studies have shown that miR-224 is more highly expressed in not only HCC but also esophageal cancer, non-small cell lung cancer, colorectal cancer, cervical cancer and glioma, and this molecule has a proliferative effect on these cancer cells through direct interactions with various tumor-suppressor genes, such as CAMKK2, ADAM17, Homeobox D 10 and RKIP [63][64][65][66][67][68]. Moreover, the clinical relevance of miR-224 had been reported as an indicator of chemoresistance to cisplatin, methotrexate and R-CHOP, radiation sensitivity and a prognostic factor of sorafenib-treated patients [69][70][71][72][73][74]. These findings strongly suggest that miR-224 might have a pivotal role in carcinogenesis and the development of HCC tumors.…”
Section: Discussionmentioning
confidence: 99%